Absorbable suture made from rice starch - Punyanitya S. (2014)
The main objective of this work is to make an absorbable monofilament suture from Thai rice starch. The improvement of the mechanical properties of Thai rice starch polymer films were achieved by addition of small amount of gelatin, carboxymethylcellulose (CMC) and carbon nanopowders. The carbon nanopowders were produced from coconut shell in our laboratory room by milling method. The incorporation of carbon nanopowders with a high aspect ratio and/or an extremely large surface area into Thai rice starch polymer films improves their mechanical performances significantly. Additionally, the black color from carbon nanopowder is easily visualized in tissue during surgery. The manufacturing processes are very simple by blending of the raw materials in hot water and then dry heating in electric oven. The final product was characterized of microstructures and mechanical properties. The resulting Thai rice starch-carbon nanocomposites possess several advantages for manufacture of sutures: 1. high water resistance that can be uses in the human body. 2. high mechanical strength that appropriate to manufacture of sutures. 3. biocompatibility and bioabsorbable. 4. low cost. 5. Eco-friendly green nanocomposites. However, the method of size designation of sutures fibers and needle attachment are the problem which restricts our suture in really applications. The investigation of knowledge and simple technology of manufacture of suture and needle attachment will be performed. © (2010) Trans Tech Publications.